The lipid-lowering effects of lomitapide are unaffected by adjunctive apheresis in patients with homozygous familial hypercholesterolaemia – A post-hoc analysis of a Phase 3, single-arm, open-label trial. Issue 2 (June 2015) - Stefanutti, C.; Blom, D.J.; Averna, M.R.; Meagher, E.A.; Theron, H. dT.; Marais, A.D.; Hegele, R.A.; Sirtori, C.R.; Shah, P.K.; Gaudet, D.; Vigna, G.B.; Sachais, B.S.; et al.
Abstract: Objective: Lomitapide (a microsomal triglyceride transfer protein inhibitor) is an adjunctive treatment for homozygous familial hypercholesterolaemia (HoFH), a rare genetic condition characterised by elevated low-density lipoprotein-cholesterol (LDL-C), and premature, severe, accelerated atherosclerosis. Standard of care for HoFH includes lipid-lowering drugs and lipoprotein apheresis. We conducted a post-hoc analysis using data from a Phase 3 study to assess whether concomitant apheresis affected the lipid-lowering efficacy of lomitapide. Methods: Existing lipid-lowering therapy, including apheresis, was to remain stable from Week −6 to Week 26. Lomitapide dose was escalated on the basis of individual safety/tolerability from 5 mg to 60 mg a day (maximum). The primary endpoint was mean percent change in LDL-C from baseline to Week 26 (efficacy phase), after which patients remained on lomitapide through Week 78 for safety assessment and further evaluation of efficacy. During this latter period, apheresis could be adjusted. We analysed the impact of apheresis on LDL-C reductions in patients receiving lomitapide. Results: Of the 29 patients that entered the efficacy phase, 18 (62%) were receiving apheresis at baseline. Twenty-three patients (13 receiving apheresis) completed the Week 26 evaluation. Of the six patients who discontinued in the first 26 weeks, five were receiving apheresis. There were no significant differences in percent change from baseline of LDL-C at Week 26 in patients treated (−48%) and not treated (−55%) with apheresis (p = 0.545). Changes in Lp(a) levels were modest and not different between groups (p = 0.436). Conclusion: The LDL-C lowering efficacy of lomitapide is unaffected by lipoprotein apheresis. Highlights: Lomitapide is an adjunctive treatment for homozygous familial hypercholesterolaemia (HoFH). Standard of care for HoFH includes lipid-lowering drugs and lipoprotein apheresis. The LDL-C lowering efficacy of lomitapide is not affected by plasma or lipoprotein apheresis.